2011
DOI: 10.2106/jbjs.h.00103
|View full text |Cite
|
Sign up to set email alerts
|

Patellar Subluxation at Terminal Knee Extension: Isolated Deficiency of the Medial Patellomeniscal Ligament

Abstract: Isolated deficiency of the medial patellomeniscal ligament can be detected by physical examination. Restoration of the normal length of the ligament by plication can lead to resolution of detectable patellar subluxation and its associated symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
0
21
0
5
Order By: Relevance
“…2 In the study by Philippot et al, the combined importance of the MPTL and MPML was evaluated rather than the isolated actions of each of these ligaments. In a clinical study, Garth et al 7 observed the presence of clinical and arthroscopic subluxation in patients with isolated MPML lesions with the knee in extension. Thus the MPTL and MPML are important in maintaining normal kinematics of the patellofemoral joint in all ranges of motion, especially at extension and higher degrees of flexion.…”
mentioning
confidence: 99%
“…2 In the study by Philippot et al, the combined importance of the MPTL and MPML was evaluated rather than the isolated actions of each of these ligaments. In a clinical study, Garth et al 7 observed the presence of clinical and arthroscopic subluxation in patients with isolated MPML lesions with the knee in extension. Thus the MPTL and MPML are important in maintaining normal kinematics of the patellofemoral joint in all ranges of motion, especially at extension and higher degrees of flexion.…”
mentioning
confidence: 99%
“…Isso ocorreu principalmente devido ao LPFM ser o restritor primário à translação lateral da patela (3)(4)(5) . No entanto, apesar de serem restritores secundários, o LPTM e o LPMM, tem uma contribuição importante na manutenção da estabilidade da articulação PF, principalmente na fase final da extensão, quando contrapõe a tração próximo-lateral do quadríceps (67,78) , e nos maiores graus de flexão, quando é tensionado e aumenta sua colaboração na restrição da translação lateral da patela (34) . Além disso, é importante para preservação de um trajeto patelar adequado através da manutenção da inclinação e rotação patelar normal (34) .…”
Section: Discussionunclassified
“…Como o LPFM, o LPTM e o LPMM compartilham muitas características semelhantes acreditamos que a reconstrução do LPTM também deve ser melhor do que seu reparo. Além disso, há apenas um estudo clínico que mostra bons resultados com o reparo do LPMM (78) enquanto muitos mostram bons resultados com reconstruções do LPTM (63,64,66,67,69,70,72,74,77,80,(89)(90)(91).…”
Section: Discussionunclassified
See 2 more Smart Citations